Anxious Joburg : The inner lives of a global South city - Van Staden, Cobus; Van Staden, Cobus; Falkof, Nicky; Falkof, Nicky (Book collections on Project MUSE., 2020)
Anxious Joburg focuses on Johannesburg, the largest and wealthiest city in South Africa, as a case study for the contemporary global south city. Global south cities are often characterised as sites of contradiction and difference that produce a range of feelings around anxiety. This is often imagined in terms of the global north's anxieties about the south: migration, crime, terrorism, disease and environmental crisis. Anxious Joburg invites readers to consider an intimate perspective of living inside such a city. How does it feel to live in the metropolis of Johannesburg: what are the conditions, intersections, affects and experiences that mark the contemporary urban? Scholars, visual artists and storytellers all look at unexamined aspects of Johannesburg life. From peripheral settlements to the inner city to the affluent northern suburbs, from precarious migrants and domestic workers to upwardly mobile young women and fearful elites, Anxious Joburg presents an absorbing engagement with this frustrating, dangerous, seductive city. It offers a rigorous, critical approach to Johannesburg revealing the way in which anxiety is a vital structuring principle of contemporary life. The approach is strongly interdisciplinary, with contributions from media studies, anthropology, religious studies, urban geography, migration studies and psychology. It will appeal to students and teachers, as well as to academic researchers concerned with Johannesburg, South Africa, cities and the global south. The mix of approaches will also draw a non-academic audience.